ENHANCING CRITICAL THINKING SKILLS THROUGH HISTORY EDUCATION AND DIGITAL LITERACY IN THE TECHNOLOGICAL ERA 4.0 - Soviano Dwi Edwinson; Alfian Dimassaujana (CV. Fahr Publishing, 2024)
The development of Information and Communication Technology (ICT) is currently developing rapidly and rapidly. With the existence of Information and Communication Technology, to get any information you want to search for, you can access it via laptops, cellphones and so on that are connected to the internet network. Use a mixed approach (mixed methods) which combines quantitative and qualitative methods to get comprehensive data. Activities in learning at school effectively by an educator can create a pleasant learning process. The effectiveness of learning is a measure of the success of a school in providing education, so it is very necessary to have learning efforts that are able to arouse children's interest and willingness in learning activities to develop all the potential in children. which is combined with the five aspects of development and instilling strong religious values ​​in the child (Rohmawati, 2015). From the results of this research it can be concluded that the existence of Information and Communication Technology is very beneficial for the world of education. And based on the results of distributing questionnaires to respondents in the history education study program.